2016
DOI: 10.1002/asi.23754
|View full text |Cite
|
Sign up to set email alerts
|

Understanding users of cloud music services: Selection factors, management and access behavior, and perceptions

Abstract: Recent, rapid changes in technology have resulted in a proliferation of choices for music storage and access. Portable, web‐enabled music devices are widespread, and listeners now enjoy a plethora of options regarding formats, devices, and access methods. Yet in this mobile music environment, listeners' access and management strategies for music collections are poorly understood, because behaviors surrounding the organization and retrieval of music collections have received little formal study. Our current res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…The first example is music exploration and discovery activity, which is one of the most important information practices in cloud music services (Lee et al , 2017). As shown in Figure 3, the subject of these information activities is music listeners; the object is music and music-related information (e.g.…”
Section: The Case Of Wanyi Yun Musicmentioning
confidence: 99%
“…The first example is music exploration and discovery activity, which is one of the most important information practices in cloud music services (Lee et al , 2017). As shown in Figure 3, the subject of these information activities is music listeners; the object is music and music-related information (e.g.…”
Section: The Case Of Wanyi Yun Musicmentioning
confidence: 99%
“…Lee, Cho and Kim (2016) found that 82.2% of the respondents searched for music they heard on streaming services, while 21.1% of the respondents used music-related apps (such as Pandora or Spotify) almost every day (13.2%), or a few times per week (7.9%). Lee et al (2017), in their interviews (of 20 adults and 20 teen users), investigated music information behaviour in cloud-based systems and revealed that the most popular cloud services among respondents were Google Play Music, Apple iCloud, Amazon Cloud, Google Drive and Dropbox, which they mostly used for listening to their collections. Furthermore, participants also used streaming sites such as Spotify, Pandora and YouTube for discovering and listening to music for different purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for music tasks, perceived task difficulty in music research is affected by task complexity, user background, system affordances, task uncertainty and enjoyability in the study of Hu et al [24]. There is growing consensus that user-based analysis and information behavioural researches are key to promoting the design of MIR systems [25]. For example, Lee and Price [26] explored how users interacted with MIR system and evaluated their experience with the music services.…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%